A necessary evil : a novel - Mukherjee, Abir (Mukherjee, Abir. Sam Wyndham, 2018)
Sam Wyndham is visiting the kingdom of Sambalpore, home to diamond mines and the beautiful Palace of the Sun. But when the Maharaja<U+2019>s eldest son is assassinated, Wyndham realises that the realm is riven with conflict. Prince Adhir was unpopular with religious groups, while his brother <U+2013> now in line to the throne <U+2013> appears to be a feckless playboy. As Wyndham and Sergeant <U+2018>Surrender-not<U+2019> Banerjee endeavour to unravel the mystery, they become entangled in a dangerous world. They must find the murderer, before the murderer finds them.